Perception Index of Muhammadiyah Ideology: A Survey on Al-Islam and Kemuhammadiyahan Values and Understandings - Arqam, Mhd Lailan; Suwarno, Rahmadi Wibowo; Shalihin, Rahmat Ryadhush (Letiges, 2023)
This study aimed to investigate the perception index of lecturers at Ahmad Dahlan University (UAD), a part of Muhammadiyah Higher Education (PTM), regarding the Muhammadiyah ideology. The scope of the ideology includes the Statutes of Muhammadiyah (MADM), Muhammadiyah characteristics, and Muhammadiyah's Beliefs and Ideals of Life (MKCHM). This study utilized a quantitative research method, specifically the f-type descriptive survey. The population of this study comprised all UAD lecturers, totalling approximately 900 individuals, with a sample size of 300 respondents. The sampling technique employed was probability sampling, precisely proportionate stratified random sampling. The results indicated that UAD lecturers' understanding of the ideology fell within the moderate category, with an average value of 70% among the total sample of 132 lecturers. Meanwhile, the ideological understanding map revealed a medium type, with Muhammadiyah characteristics scoring 74%, MADM ideology scoring 68%, and MKCHM ideology scoring 70%. The research's implications serve as the foundation for ideological development among lecturers, program development, and the enhancement of the AIK curriculum at UAD in general, as well as for the curriculum of the Master of Islamic Education study program.